2014
DOI: 10.31671/dogus.2018.83
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Economic Growth and Stock Returns : Evidence From Turkey

Abstract: Financial development is one of the most important determinants of the economic development. Financial developments in Turkey began in the early 1980s and still have continued. During this period, it has survived a severe interaction between financial development and economic growth. In this study, the causality relationship between stock returns and economic growth in Turkey it was analysed over the period 1998Q2-2014Q2. In this context; firstly, Bootstrapped Toda-Yamamoto and Frequency Domain causality tests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 6 publications
0
3
1
Order By: Relevance
“…Ouma and Muriu (2014) showed that all macroeconomic variables influence the market positively except interest rate and only Kirui et al (2014) revealed contrary results that gross domestic product, inflation, and interest rate do not influence stock return. Results also conform to Senturk et al (2014) and Kirui et al (2014). However, the results are not consistent with the results by Giri and Joshi (2017) and Ouma and Muriu, which found out that economic growth and inflation rate influence stock prices positively…”
Section: Oimcontrasting
confidence: 60%
See 1 more Smart Citation
“…Ouma and Muriu (2014) showed that all macroeconomic variables influence the market positively except interest rate and only Kirui et al (2014) revealed contrary results that gross domestic product, inflation, and interest rate do not influence stock return. Results also conform to Senturk et al (2014) and Kirui et al (2014). However, the results are not consistent with the results by Giri and Joshi (2017) and Ouma and Muriu, which found out that economic growth and inflation rate influence stock prices positively…”
Section: Oimcontrasting
confidence: 60%
“…Empirical studies such as Ouma and Muriu (2014), Giri and Joshi (2017), Senturk et al (2014) and Kullaporn and Lalita (2010) all asserted that macroeconomic factors significantly influence stock return except Kirui et al (2014) who observed that macroeconomic factors insignificantly influence stock return. The reviewed studies such as Garba (2014), Kamini andMalhotra (2013), Al-Masum (2014), Adam et al (2014), Nicol (2013), Farzand et al (2015 and Kang et al (2019) all revealed that dividend policy significantly influences stock return in Nairobi Securities Exchange and that none studies reviewed used macroeconomic factors as mediating variable between dividend policy and stock return in Nairobi Securities Exchange, an investigation of how macroeconomic factors affect the relationship between dividend policy and stock return in Nairobi Securities Exchange became essential.…”
mentioning
confidence: 99%
“…However, looking at Turkey's economic past, it becomes clear that the nation has experienced multiple economic crises (Demir, 2019). Although there have been significant correlations between economic growth and financial markets in Turkey since 2002, numerous unfavourable political developments have impacted economic growth and financial stability (Şentürk, Özkan & Akbaş, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the data for Japan shows that CPI and discount rate are insignificant Humpe and MacMillan (2009). state that the results from the US data were expected based on existing theory.Using a different methodology,Şentürk, Özkan and Akbaş (2014) sought to determine causality between economic growth and share returns on the Borsa Istanbul 100 Index and Turkey's Gross Domestic Product (GDP) from quarter 2 in 1998 to quarter 2 in 2014. The Bootstrapped Toda-Yamamoto causality test results showed no causality between the variables; however, the Frequency Domain causality test showed that there was a connection…”
mentioning
confidence: 99%